ANALYSIS OF THE INFLUENCE OF AUDIT TENURE, FINANCIAL DISTRESS, AUDIT COMMITTEE, AUDIT QUALITY AND AUDIT OPINION ON AUDIT DELAY IN PROPERTY AND REAL ESTATE SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE (IDX) 2018-2022 - ,; ,; ,; ,; , (Bilancia : Jurnal Ilmiah Akuntansi; Vol 8 No 3 (2024): Bilancia : Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine and analyze the influence of audit tenure, financial distress, audit committee, audit quality and audit opinion on audit delay in Property and Real Estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The population in this study were all Property and Real Estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022 and a sample of 240 samples taken using a purposive sampling technique. Data analysis in research uses multiple linear regression data analysis methods. Based on the research results, the results show that audit tenure has a positive and insignificant influence on audit delay, financial distress has a negative and insignificant influence on audit delay, the audit committee has a positive and significant influence on audit delay, audit quality has a positive and insignificant influence on audit delay and audit opinion have a negative and significant influence on audit delay. Keywords: Audit Tenure, Financial Distress, Audit Committee, Audit Quality, Audit Opinion, Audit Delay Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh audit tenure, financial distress, komite audit, kualitas audit dan opini audit terhadap audit delay pada perusahaan sektor Property dan Real Estate yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2018-2022. Populasi dalam penelitian ini adalah seluruh perusahaan sektor Property dan Real Estate yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2018-2022 dan sampel sebanyak 240 sampel yang diambil dengan menggunakan teknik purposive sampling. Analisis data dalam penelitian menggunakan metode analisis data regresi linier berganda. Berdasarkan hasil penelitian diperoleh hasil bahwa audit tenure berpengaruh positif dan tidak signifikan terhadap audit delay, financial distress berpengaruh negatif dan tidak signifikan terhadap audit delay, komite audit berpengaruh positif dan signifikan terhadap audit delay, kualitas audit berpengaruh positif dan tidak signifikan terhadap audit delay dan opini audit mempunyai pengaruh negatif dan signifikan terhadap audit delay. Kata Kunci : Audit Tenure, Financial Distress, Komite Audit, Kualitas Audit, Opini Audit, Audit Delay